Dielectric behavior of CaCu3Ti4O12 electro-ceramic doped with La, Mn and Ni synthesized by modified citrate-gel route - Singh L.; Rai U.S.; Rai A.K.; Mandal K.D. (My University, 2025)
The effect of La3+, Mn2+ and Ni2+ doped calcium copper titanate, CaCu3Ti4O12 (CCTO), at higher concentrations (CR1 and CR2 with 5 mol% and 10 mol%, respectively), has been examined by semi-wet route at relatively lower temperature. This semi-wet route employs citrate-nitrate gel chemical method using TiO2 solid powders. X-ray diffraction (XRD) analysis confirms the formation of single phase in the doped samples sintered at 900 °C for 8 h. Scanning electron micrographs (SEM) show that the average grain size for CR2 is larger than that of CR1 composition. The energy dispersive X-ray spectroscopy (EDX) is used to study the percentage compositions of different ions present in both ceramics. Dielectric constant (ɛr) and dielectric loss (tanδ) values of CR1 are comparatively higher than those of CR2 ceramic at all measured frequencies and temperatures. The nature of temperature-dependent relaxation behavior of the ceramics is also studied by impedance, modulus spectroscopic analysis and confirms Maxwell-Wagner relaxation. © 2013, The Author(s).